2014
DOI: 10.1088/0004-637x/790/2/107
|View full text |Cite
|
Sign up to set email alerts
|

CONDITIONS FOR OCEANS ON EARTH-LIKE PLANETS ORBITING WITHIN THE HABITABLE ZONE: IMPORTANCE OF VOLCANIC CO2DEGASSING

Abstract: Earth-like planets in the habitable zone (HZ) have been considered to have warm climates and liquid water on their surfaces if the carbonate-silicate geochemical cycle is working as on Earth. However, it is known that even the present Earth may be globally ice-covered when the rate of CO 2 degassing via volcanism becomes low. Here we discuss the climates of Earth-like planets in which the carbonate-silicate geochemical cycle is working, with focusing particularly on insolation and the CO 2 degassing rate. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
77
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(80 citation statements)
references
References 27 publications
3
77
0
Order By: Relevance
“…Kadoya & Tajika 2014Foley & Driscoll 2016). From the point of view of modelling of the interior, the most important difference between our approach and those above is that we assume our planet to operate in a stagnant-lid mode of convection rather than in the mobile-lid (or active-lid) mode realized through plate tectonics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kadoya & Tajika 2014Foley & Driscoll 2016). From the point of view of modelling of the interior, the most important difference between our approach and those above is that we assume our planet to operate in a stagnant-lid mode of convection rather than in the mobile-lid (or active-lid) mode realized through plate tectonics.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, even the Earth, where plate tectonics and a carbon-silicate cycle are active, could become uninhabitable by turning into a snowball if the degassing rate of CO 2 from the interior becomes too low (Tajika 2007;Kadoya & Tajika 2014. On the other hand, the very way in which plate tectonics operates on Earth, when it started, and whether it is a stable or a transient feature in the tectonic history of our planet are all complex and still controversial matters (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…At the outer edge, the models assume the regulation of the climate by the carbonate-silicate cycle. Recent calculations have suggested that planets in the outer regions of the HZ may be less likely to maintain stable, warm climates, but instead may oscillate between long, globally glaciated states and shorter periods of climatic warmth (Kadoya & Tajika 2014, 2015Menou et al 2015;Haqq-Misra et al 2016). Such conditions, similar to "Snowball Earth" episodes experienced on Earth, would be detrimental to the development of complex land life.…”
Section: Discussionmentioning
confidence: 99%
“…Snowball Earth events are an acute stressor on life, but may actually increase the complexity of life through evolutionary pressure (Kirschvink 1992;Hoffman et al 1998) and by increasing the atmospheric oxygen concentration (Hoffman & Schrag 2002;Laakso & Schrag 2014, 2017 that might act as biosignatures to remote astronomers. Moreover, planets in the habitable zone with low levels of CO 2 outgassing may experience limit cycles between habitable and snowball climate states (Kadoya & Tajika 2014;Menou 2015;Haqq-Misra et al 2016;Batalha et al 2016;Abbot 2016;Paradise & Menou 2017). It is therefore important to understand the transitions into and out of snowball events for tidally locked planets.…”
Section: Introductionmentioning
confidence: 99%